(untitled) (Acta Scientiarum. Animal Sciences, 2019)
We evaluated meat quality and color of breast during storage in ducks fed diet supplemented with different forms of Houttuynia cordata (HC) with fermented red koji (FRK). In total, 240 one-day-old Pekin ducks (160 males and 80 females) were allocated to four diet treatments (control, 1% HC powder mixed with FRK, pelleted 1% HC with FRK, and coated pellets of 1% HC with FRK). At days 3 and 7 of storage, pH values were slightly influenced (p < 0.05) by different forms of HC with FRK, but was no influence at day 0 of storage day. Diet treatments with different forms of HC and FRK had an effect (p < 0.05) on TBARS values at 0, 3, and 7 days of storage and DPPH radical-scavenging activity at 0 days of storage, except for cooking loss. Overall, in breast meat of ducks, L* values at day 3 of storage and a* values at day 0 of storage were significantly influenced (p < 0.05) by treatments with different forms of HC and FRK. In conclusion, using either 1% HC and FRK pellets or pellets coated with HC and FRK at 1% resulted in a decrease in TBARS values and an increase in DPPH radical-scavenging activity during storage.